Efektivitas Pemberian Edukasi Untuk Meningkatkan Peran Keluarga dalam Merawat Klien dengan Skizofrenia di Puskesmas Kuranji Padang - Edo Gusdiansyah; Welly; Yuanita Ananda (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2022)
People with Mental Disorders are people who experience disturbances of thought, behavior and feelings that cause distress, functional distress and reduce quality of life (Mental Health Law No. 18 of 2014). The prevalence of severe mental disorders based on the 2018 Basic Health Research (Riskesdas) in the Indonesian population is 7 per mile. The heaviest mental disorders are known as psychotic disorders/schizophrenia. From this number, one in ten families have problems in caring for family members who have schizophrenia problems that require good education in caring for family members. Therefore, it is very necessary to provide a method for providing education in increasing the role of families in caring for family members with schizophrenia problems which aims to help increase knowledge and the role of families in treating mental health problems, especially schizophrenia problems. The implementation of education is carried out in 4 sessions. This activity was carried out on July 15, 2021 with 20 families participating. The results of the evaluation showed that there was an increase in the knowledge and role of the family in caring for their family members during the pretest and posttest. Suggestions for the puskesmas are to monitor the results of this education and improve education to families by scheduling.